Asuhan Keperawatan Pada Ny. M dengan Gangguan Sistem Persarafan: Edema Serebri di Ruang Gladiol Atas RSUD Sukoharjo - Adhita, Arief, Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2015)
NURSING CARE OF MRS. M WITH NEUROLOGIC SYSTEM PROBLEM: EDEMA CEREBRI IN GLADIOLWARD SUKOHARJO HOSPITAL (Arief Adhita, 2015, 67 pages) ABSTRACT Background: Head injury is still a global health problem as the cause of death, disability, and mental deficits at a young age. Head injury sufferers often experience edema cerebri i.e the accumulation of excess fluid in the brain extracellular or intracelluler spaces or intracranial hemorraghe resulting in increased intracranial pressure. Objective: Knowing about the study of nursing care with edema cerebri and able to apply it in patiens with edema cerebri includes assessement, diagnose intervention, implementation and evaluation of nursing. Method: The research is an assesment. Data is obtained by using interview and physical examination on edema cerebri patient. Result: After assasment obtained three problems namely, pain, distruption of normal sleep patterns, and anxious. The author makes an intevention to prevent an increase in intracranial pressure, improve sleep quality and anxiety. Implementations have largery done, all problems can be resolved most and need further treatment so that the problem can be completely resolved. Conclusing: On nursing care process all problem are can be overcome but jud partly of problem, so need to continue nursing care and cooperation with medical team, patient and family was very need to successfuly nursing care Key Words: Edema cerebri, tissue perfusion, sleep patterns, anxious.